Reframing Property Tax as Excise under Capital Mobility Conditions - Alijon Akmal ugli, Turayev; Diyorbek , Normukhammadov (Research Parks Publishers, 2025)
This study examines the conceptual and practical classification of excise taxes, with a particular focus on the property tax, drawing on Peter Mieszkowski’s foundational analysis of tax incidence. While excise taxes are conventionally understood as levies on specific goods or services, this research identifies a critical knowledge gap in distinguishing excise taxes from profit-based taxation, especially in the context of immobile capital. Using a dual-method approach that combines theoretical modelling with empirical data from OECD countries, the study analyses how factor mobility influences whether a property tax functions as an excise or a profits tax. The findings reveal that in settings with immobile capital, the property tax behaves like a tax on capital usage, thus mirroring excise characteristics, whereas in economies with mobile capital, it acts more like a profits tax. These results have important implications for fiscal policy design, particularly for ensuring tax equity and minimising economic distortions. The study underscores the need for context-specific tax classifications and recommends further investigation into the effects of globalisation and digitalisation on modern excise tax structures.